Réponses

2013-10-24T14:39:23+02:00
1) 4 x^{2} - 16 + ( 2x + 3 ) ( x - 2 )
= 4x^2 - 16 + 2x * x + 2x * (-2) + 3 * x + 3 * (-2)
= 4x^2 - 16 + 2x^2 - 4x + 3x - 6
= 6x^2 - 22 - 1x

2) ( 6x + 3 ) - ( x - 4 ) ( 2x + 1 )
= 6x + 3 - x * 2x + x * 1 + (-4) * 2x + (-4) * 1
= 6x + 3 - 2x^2 + 1x - 8x - 4
= -1x - 2x^2 - 1
merci beaucoup :)
pour le 1 : 4x²-16+(2x+3)(x-2)= (2x-4)(2x+4)+(2x+3)(x-2)=2(x-2)(2x+4)+(2x+3)(x-2)=(x-2)(4x+8)+(2x+3)(x-2)=(x-2)(4x+8+2x+3)=(x-2)(6x+11)
Merci pour votre correction :)
Bonjour, c'est normal je ne fais pas la course aux points et aux classements... c'est plus sympa